Characterization of Salacca Zalacca for Dye Sensitized Solar Cell (DSSC) - Wendri, Nyoman; Ekayani Sri Tussniari, Putu; Suyanto, Hery (BULETIN FISIKA; Vol 20 No 2 (2019): BULETIN FISIKA, 2019)
Snake fruit (salacca zalacca) characterization for Dye Sensitized Solar Cell (DSSC) material was conducted using Fourier transform Infrared (FTIR) and Principle Component Analysis (PCA) method. Dragon fruit and mangos teen were used as validator since they are containing anthocyanin. Data shows that snake fruit and mangos teen are in one cluster. Therefore, snake fruit can be used as DSSC material. DSSC fabrication using sandwich method that contains counter electrode, electrolyte and working electrode. The working electrode was made of thin film of titanium dioxide (TiO 2 ) into indium Tin Oxide (ITO) which then was soaked in dye snake fruit as time function of 6, 12 and 24 hours. Result showed that the longer time of soaking, the current and efficient increased. In twenty four hours soaking, the current, voltage and efficiency were 6 mA, 9.16 V and 0.011 % respectively.